Біологічні методи оцінки екологічного стану ґрунтів біля авіапідприємств - Маджд, С.М.; Франчук, Г.М. (Екологічна безпека та природокористування, 2012)
Results of biological methods of an estimation of definition of toxicity of ground in territories adjoining to aviation enterprises are presented. It is lead quality standard of a soil cover on biotests of different trophic levels. It is certain toxicity of ground in vicinities of aviation enterprises.